Essential Soft Skills for Fresh Graduate Engineers: Bridging the Gap Between Academia and Industry (Comprehensive Journal of Science, 2025)
The transition from academia to the professional engineering world is a critical phase for fresh graduate engineers. While technical knowledge and expertise are fundamental, the importance of soft skills cannot be overstated. This article explores the essential soft skills that fresh graduate engineers should possess to thrive in the competitive and dynamic engineering industry. These skills include communication, teamwork, problem-solving, adaptability, emotional intelligence, and time management. The article also discusses the role of educational institutions and industry in fostering these skills and provides recommendations for graduates to develop and refine them.
Keywords: soft skills, fresh graduate engineers, engineering education.